Developing action capacity for sufficient consumption among Europeans facing unequal conditions - Boström, Magnus; Strid, Sofia; Zorell, Carolin; Balkmar, Dag (Frontiers in Sustainability, 2025)
This article investigates the conditions under which action-capacity for changing lifestyle patterns toward sufficient consumption can be developed in Europe. The study departs from the recognition that current volumes and patterns of consumption are unsustainable, and that radical lifestyle changes are needed at individual, community, and societal levels. At the same time, European societies are marked by deepening inequalities, with many people living in poverty and hardship who have limited incentives to reduce their already restricted consumption. Against this backdrop, the article asks how bottom-up action-capacity for sustainability transformations can emerge under conditions of constraint. Drawing on theories of efficiency and sufficiency in sustainable consumption, the improve/shift/avoid framework, and concepts of socially embedded agency and reflexivity, the article examines two key domains of the green transition: food (farm-to-fork) and mobility (sustainable transport). The empirical analysis is based on 220 narrative interviews from ten European countries (Austria, Belgium, Germany, Greece, Italy, Norway, Portugal, Romania, Sweden, and Turkey), encompassing people with diverse life situations, including in relative poverty. The findings show that while many narratives reflect efficiency-oriented approaches, they also reveal a wide range of sufficiency strategies. Across contexts, several features of action-capacity were identified, including imagination, responsibility, reflexivity, adaptive capacity, independence, and the pursuit of quality. The article concludes that fostering action-capacity for sufficient consumption and lifestyle change requires multifaceted strategies that integrate individual, social, and institutional efforts, while directly addressing inequalities.